Edukasi Hukum Penghapusan Kekerasan dalam Rumah Tangga untuk Peningkatan Ketahanan Keluarga: Legal Education on Eliminating Domestic Violence to Increase Family Resilience - Haryadi, Dwi; Adha, Muhammad Yogie; Suntara, Reza Adriantika (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Domestic violence among Indonesians, especially in Bangka Belitung, is a serious concern. The lack of legal literacy regarding the impacts and factors of domestic violence is one of the causes of the continued prevalence of domestic violence. Therefore, the community service team aims to encourage the elimination of domestic violence in the Tebing Village area, Kelapa District, West Bangka Regency, as part of efforts to increase family resilience. This activity was carried out using a participatory, dynamic socialization method and case study analysis. The participatory approach in this activity aims to encourage the community to be more open to recognizing and reporting acts of violence. The activity was carried out in three stages: preparation, implementation, and evaluation. The results of this service are increased public knowledge about the types of domestic violence and the criminal threats under Law Number 23 of 2004 concerning the Elimination of Domestic Violence, as well as increased awareness that domestic violence is not only a personal matter, but a social problem and a form of legal violation with broad impacts.